Analytical performance validation of a coronary heart disease risk assessment multi-analyte proteomic test. (March 2013) - Nolan, Niamh; Tee, Lilian; Vijayakumar, Swathi; Burazor, Ivana; Hytopoulos, Evangelos; Biggs, William H; Beggs, Michael; French, Cynthia; Harrington, Douglas S
<x xml:space="preserve">Abstract</x> Background: Coronary heart disease (CHD) remains prevalent despite efforts to improve CHD risk assessment. The authors developed a multi-analyte immunoassay-based CHD risk assessment (CHDRA) algorithm, clinically validated in a multicenter study, to improve CHDRA in intermediate risk individuals. Objective: Clinical laboratory validation of the CHDRA biomarker assays' analytical performance. Methods: Multiplexed immunoassay panels developed for the seven CHDRA assays were evaluated with donor sera in a clinical laboratory. Specificity, sensitivity, interfering substances and reproducibility of the CHDRA assays, along with the effects of pre-analytical specimen processing, were evaluated. Results: Analytical measurements of the CHDRA panel proteins (CTACK, Eotaxin, Fas Ligand, HGF, IL-16, MCP-3 and sFas) exhibited acceptable accuracy (80 – 120%), cross-reactivity (< 1%), interference (< 30% at high concentrations of bilirubin, lipids, hemoglobin and HAMA), sensitivity and reproducibility (< 20% CV across multiple runs, operators and instruments). Recoveries from donor sera subjected to typical clinical laboratory pre-analytical conditions were within 80 – 120%. The pre-analytical variables did not substantively impact the CHDRA scores. Conclusions: The CHDRA panel analytical validation in a clinical laboratory meets or exceeds the specifications established during the clinical utility studies. Risk score reproducibility across multiple test scenarios suggests the assays are not susceptible to clinical laboratory pre-analytical and analytical variation.